Rock music and rocker's lifestyles : looking at the social representations in the Portuguese contemporary society - Martins, Ana (2022)
As we know, rock performances and lifestyles have frequently been linked to a whole series of disorders, substance uses and abuses, and risk behaviours, commonly expressed in the epitome of sex, drugs and rock'n'roll. In this context, there are countless enumerations of these themes in the lyrics and videos of artists or rock bands, and there is also a fascination with the mythical stories of rock and roll, its bohemian life, and the refusal to adopt conventional behaviours. These legends and narratives are crucial to the daily experiences of fans, particularly young people. In this context, this analysis aims to explain and understand the social representations and practices incorporated with the sex-drugs-rock trichotomy in contemporary Portuguese society. In other words, this article intended to explore the stereotypes, feelings, and interpretations associated with sexual behaviours and the consumption of illegal substances within the rock universe in a context of late modernity.